Multilevel theorizing in international business: the case of research on strategy implementation in MNCs. Issue 4 (9th December 2020) - Šilenskytė, Aušrinė; Smale, Adam
Abstract : Purpose: This paper aims to illustrate why an understanding of how levels of analysis interact is an essential part of multilevel research in the field of international business (IB). Using research on strategy implementation (SI) in multinational corporations (MNCs) as an example, this paper develops a taxonomy and research agenda that demonstrates the key role critical scholars can play in advancing multilevel theorization. Design/methodology/approach: Drawing on the assumptions of methodological collectivism and individualism, the paper presents a four-step framework: defining the theoretical boundaries of the selected subject; juxtaposing theoretical arguments with empirical work; identifying single- and multi-level theories; and developing a research agenda. Findings: Research on SI in MNCs has been dominated by one type of theorizing that focuses on the designs of organizational systems or the power of institutions. Multilevel theorization grounded in methodological individualism would offer new knowledge by including the views of under-represented stakeholders, questioning the justice of established systems and overall implications of MNC operations. Research limitations/implications: The proposed four-step framework encourages scholars to adopt a systematic approach to multilevel theorizing and draw upon the untapped potential of IB theories. Originality/value: The paper contributes to the IB field by introducing an approach to assessing IB research from a multilevel theorizing perspective. The actionable research agenda on SI and the taxonomy of SI research can assist scholars in making aligned choices on study design and envisioning research questions that yield meaningful contributions to theory and practice.